Respuesta :

For this case we have that the point-slope equation of a line is given by:

[tex]y-y_ {0} = m (x-x_ {0})[/tex]

Where:

m: It's the slope

[tex](x_ {0}, y_ {0}):[/tex]It is a point

We have to:

[tex]m = -3\\(x_ {0}, y_ {0}): (2, -5)[/tex]

Substituting:[tex]y - (- 5) = - 3 (x-2)\\y + 5 = -3 (x-2)\\y + 5 = -3x + 6\\y = -3x+1[/tex]

ANswer:

[tex]y + 5 = -3 (x-2)\\y = -3x+1[/tex]

ANSWER

[tex]y = - 3x + 1[/tex]

or

[tex]3x + y = 1[/tex]

EXPLANATION

The equation is calculated using the formula,

[tex]y-y_1=m(x-x_1)[/tex]

where m=-3 is the slope and

[tex](x_1,y_1) = (2, - 5)[/tex]

We substitute the the values to get:

[tex]y- - 5= - 3(x-2)[/tex]

Expand

[tex]y + 5= - 3x + 6[/tex]

[tex]y = - 3x + 6 - 5[/tex]

[tex]y = - 3x + 1[/tex]

This is the slope-intercept form.

Or in standard form;

[tex]3x + y = 1[/tex]